Automated surveillance in distributed, wireless visual networks: a comparative study - Ahmed, Tarem; Ahmed, Supriyo; Pathan, Al-Sakib Khan (2013)
A number of algorithms have been recently proposed for automatic intruder detection from CCTV images. Past researchers have tested these algorithms on centralized networks where all images are transmitted to a central control room. This paper demonstrates the applicability of a selection of such algorithms to a distributed network of wireless visual sensors. An empirical comparative study of the most popular of such algorithms on a simulation of a wireless sensor network is presented. In addition, this paper provides further evidence in support of the most effective of such algorithms to the problem of anomaly detection in image streams.